Perencanaan Pengembangan Daerah Wisata dan Oongan Sebagai Community Based Tourism di Kota Denpasar - A.A Gede Willy Tika Kencana Putra; Nyoman Diah Utari Dewi (Public Inspiration : Jurnal Administrasi Publik, 2024)
The potential for Dam Oongan to be developed as a tourist attraction includes a beautiful garden around Dam Oongan, jogging tracks, swimming pools, culinary tours located around Dam Oongan. The Oongan Dam development plan can be implemented in the development of community-based tourism objects. The problems in this study include (1) What potential attractions exist around the Oongan Dam as a community-based tourism object in Denpasar City, Bali?; and (2) What is the plan for the development of the Oongan Dam as a community-based tourism object in the City of Denpasar, Bali? This research uses the type and approach of qualitative research. The reason for using a qualitative research design is because in essence it is observing people in their environment, in this case the Oongan Traditional Village community. Data analysis technique used qualitative data analysis techniques with interactive models from Miles and Huberman. The results of the study show (1) the attractiveness potentials around Oongan Dam as a community-based tourism object in the City of Denpasar Bali seen from the internal analysis of strengths (strength) include (a) accessibility which is well available; (b) amenities (tourism support facilities) are properly available; (c) available attractions Dam Oongan, Taman Dam Oongan for jogging and shelter, Dam Oongan bridge, Pura Dalem Bugbugan Pucuk Danu, has the potential as a pre-wedding spot, and has the potential to become a tourist icon in Denpasar which is well available, the existence of a swimming pool Oongan Dam which still needs to be developed to become a national/international standard; and (d) ancillary (institutional), that is, there is no institution that specifically manages the development of Oongan Dam as a tourist attraction; and (2) the plan to develop Dam Oongan as a community-based tourism object in Denpasar City, Bali has not been fully implemented considering that the management institution has not yet been formed, community values are still unclear, vision formulation has not been carried out, attractions have been well identified but there are still weaknesses.